Early antiretroviral therapy in children perinatally infected with HIV: a unique opportunity to implement immunotherapeutic approaches to prolong viral remission. Issue 9 (September 2015) - Klein, Nigel; Palma, Paolo; Luzuriaga, Katherine; Pahwa, Savita; Nastouli, Eleni; Gibb, Diane M; Rojo, Pablo; Borkowsky, William; Bernardi, Stefania; Zangari, Paola; Calvez, Vincent; Compagnucci, Alexandra; et al.
Summary From the use of antiretroviral therapy to prevent mother-to-child transmission to the possibility of HIV cure hinted at by the Mississippi baby experience, paediatric HIV infection has been pivotal to our understanding of HIV pathogenesis and management. Daily medication and indefinite antiretroviral therapy is recommended for children infected with HIV. Maintenance of life-long adherence is difficult and the incidence of triple-class virological failure after initiation of antiretroviral therapy increases with time. This challenge shows the urgent need to define novel strategies to provide long-term viral suppression that will allow safe interruption of antiretroviral therapy without viral rebound and any associated complications. HIV-infected babies treated within a few days of birth have a unique combination of a very small pool of integrated viruses, a very high proportion of relatively HIV resistant naive T cells, and an unparalleled capacity to regenerate an immune repertoire. These features make this group the optimum model population to investigate the potential efficacy of immune-based therapies. If successful, these investigations could change the way we manage HIV infection.